Flame retarding mechanism of Polyamide 6 with phosphorus-nitrogen flame retardant and DOPO derivatives - Li, Maolin; Zhong, Yuhua; Wang, Zheng; Fischer, Andreas; Ranft, Florian; Drummer, Dietmar; Wu, Wei (Journal of Applied Polymer Science, 2016)
A novel flame-retardant composite was prepared by introducing a phosphorus-nitrogen flame retardant and DOPO-SiO2 into PA6. DOPO-SiO2 was synthesized successfully in a one-step process. PA6/OP1314/DOPO-SiO2 achieved a UL 94 V-0 rating with an LOI value of 31%. The maximum mass loss rate of decomposition decreased significantly and char residue increased to 11.6 wt % compared with that of pure PA6. The compacted and dense char was formed due to the combination of the P-N flame retardant and DOPO-SiO2. The complex viscosity of PA6/OP1314/DOPO-SiO2 increased considerably which tend to prevent the dripping phenomenon. The flame-retardant mechanism of PA6/OP1314/DOPO-SiO2 was also investigated by Fourier transform infrared spectroscopy FTIR at different temperatures and the pyrolysis products were investigated by pyrolysis gas chromatography/ mass spectrum (Py-GC/MS). It was assumed that DOPO-SiO2 and the hypophosphite of OP1314 possess excellent flame retardancy during the gaseous phase. Meanwhile, melamine and phosphate reacted with the pyrolytic products of PA6 to protect the matrix during the condensed phase.
UnivIS-Import:2016-06-01:Pub.2016.tech.FT.FT-KT.flamer
Keywords: polyamides; spectroscopy; thermogravimetric analysis (TGA)